Analisis Efisiensi Dan Produktivitas Mesin Produksi Keripik Telur Cumi (Keritcu) - Yawenda, Pahreza; Husman, Husman; Wahyudie, Ilham Ary (Jurnal Inovasi Teknologi Terapan, 2025)
This study aims to analyze the efficiency and productivity of the production machine for Keripik Telur Cumi (Keritcu), a traditional snack from Bangka made from squid eggs and sago. The research employs a quantitative approach by measuring operational time, production capacity, energy consumption, and defective product rates. Efficiency analysis was conducted using Overall Equipment Effectiveness (OEE) indicators, which include machine availability, performance, and product quality. The results show a machine efficiency rate of 75% with an average productivity of 2.5 kg/hour. The OEE value of 45% falls below the ideal industry standard (>85%), with a daily downtime of 1 hour and a product rejection rate of 10%. Improvement recommendations include reducing downtime, increasing production speed, and lowering the defect rate through machine optimization and operator training. The implementation of these recommendations is expected to enhance efficiency, productivity, and the product's competitiveness in the market.